1998
DOI: 10.1002/(sici)1097-0207(19981115)43:5<941::aid-nme435>3.0.co;2-3
|View full text |Cite
|
Sign up to set email alerts
|

Modelling of muscle behaviour by the finite element method using Hill's three-element model

Abstract: We present a numerical algorithm for the determination of muscle response by the ÿnite element method. Hill's three-element model is used as a basis for our analysis. The model consists of one linear elastic element, coupled in parallel with one non-linear elastic element, and one non-linear contractile element connected in series. An activation function is deÿned for the model in order to describe a time-dependent character of the contractile element with respect to stimulation.Complex mechanical response of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(23 citation statements)
references
References 4 publications
2
21
0
Order By: Relevance
“…We found that fiber moment arms have a considerable variation within each muscle, indicating that the common assumption that all fiber lengths and excursions within muscle are the same may not be valid, at least for the muscles examined here. Previous studies have described continuum representations of muscle 23,30,31,43 and used them, for example, to investigate intramuscular pressures 28 and understand myofascial force transmission. 48 These models represent the complex nonlinear behavior of muscle tissue; however, they have not incorporated realistic geometric arrangements of muscle fibers or muscle-bone and muscle-muscle surface contact.…”
Section: Discussionmentioning
confidence: 99%
“…We found that fiber moment arms have a considerable variation within each muscle, indicating that the common assumption that all fiber lengths and excursions within muscle are the same may not be valid, at least for the muscles examined here. Previous studies have described continuum representations of muscle 23,30,31,43 and used them, for example, to investigate intramuscular pressures 28 and understand myofascial force transmission. 48 These models represent the complex nonlinear behavior of muscle tissue; however, they have not incorporated realistic geometric arrangements of muscle fibers or muscle-bone and muscle-muscle surface contact.…”
Section: Discussionmentioning
confidence: 99%
“…However, we discovered large quantitative differences between existing models and parameters used [6,13,14,15]. Hence, it will be essential to compare these models with each other as well as with experimental data available.…”
Section: Discussion and Future Workmentioning
confidence: 99%
“…While another looks at the effect of damaged ligaments on stress urinary continence [34]. Computational models have also been developed to characterise the global behaviour of the pelvic floor muscles [35][36][37][38][39]. However, there are large quantitative differences between the models and parameters used.…”
Section: Figure 1 Anatomy Of the Anorectum Components Which Are Modementioning
confidence: 99%